2012
DOI: 10.1253/circj.cj-11-0768
|View full text |Cite
|
Sign up to set email alerts
|

Neovascularization and Angiogenic Factors in Advanced Human Carotid Artery Stenosis

Abstract: Background: Most atherosclerotic lesions are vascularized, so neovessels may also contribute to plaque progression and vulnerability, but their precise role of neovessels in atherosclerosis is still unknown. The aim of this study was to analyze the possible relationships among neovascularization, relevant angiogenic factors, and plaque vulnerability in patients with advanced carotid artery stenosis. Methods and Results:The study group comprised 56 patients (stable: n=28, unstable: n=28) with advanced carotid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 31 publications
(24 reference statements)
3
31
0
2
Order By: Relevance
“…In line with this notion, we recently demonstrated that in subjects with type 2 diabetes mellitus, symptomatic patients have lower plaque levels of PDGF and collagen than asymptomatic patients. 29 In contrast, Pelisek et al 30 analyzed the amount of PDGF in advanced human carotid artery stenosis and found no significant difference in PDGF levels between symptomatic and asymptomatic plaques.…”
Section: Discussionmentioning
confidence: 97%
“…In line with this notion, we recently demonstrated that in subjects with type 2 diabetes mellitus, symptomatic patients have lower plaque levels of PDGF and collagen than asymptomatic patients. 29 In contrast, Pelisek et al 30 analyzed the amount of PDGF in advanced human carotid artery stenosis and found no significant difference in PDGF levels between symptomatic and asymptomatic plaques.…”
Section: Discussionmentioning
confidence: 97%
“…Histological characterization of atherosclerotic plaques was performed following the hematoxylin-eosin and elastic van Gieson staining procedures to assess the pathomorphological features of all segments, as described previously [5,20,22]. Lesion stability was defi ned as described by Redgrave et al [23], considering a thin fi brous cap of less than 200 μm over a large lipid-rich atheroma as a cut-off to distinguish between stable and unstable atherosclerotic plaques ( Figure 1).…”
Section: Histological Analysis Of Atherosclerotic Plaquesmentioning
confidence: 99%
“…Namely, increased neovascularization is considered an important contributing factor for atherosclerotic plaque progression and vulnerability [5] and may explain the increased risk of atherosclerotic complications in subjects with T2DM [6,7]. Significant correlations were observed between neovascularization, plaque stability, and expression of angiogenic factors, especially vascular endothelial growth factor A (VEGF) [8].…”
Section: Introductionmentioning
confidence: 99%